Program Kreativitas Guru Dalam Meningkatkan Kemampuan Siswa Membaca Al-Qur'an Dengan Pendekatan Ekstrakurikuler BTA(Studi Kasus di SMP N 3 Kartasura Tahun Pelajaran 2016/2017) - Partini, Dewi; , Dr. Syamsul Hidayat, M.Ag (2017)
Islamic Religious Teachers have a tough challenge. The challenge was mainly in terms of instilling Akhlāqulkarīmahto students. Is not the fact of learning outcomes of Islam in the field is quite alarming? Starting from the ability to read verses of the Qur'an to the habit in their daily lives.Concerns that makes teachers have creative ideas to enhance the student's ability to read the Qur'an in SMP N 3 Kartasura and create a program of activities outside KBM is often known as extracurricular activities. BTA (Read Write Qur'an) is one of the extracurricular activities in SMP N 3 Kartasura. BTA is very important extracurricular held for students of SMP N 3 Kartasura considering the number of seventh grade students who have not been able to read fluently and correctly. Therefore, one of the efforts made by the teacher of Islamic education is to implement a program of BTA. Thus, the problem in this research is "how shape of program creativity of teachers in improving students ability to read the Qur'an through extracurricular approach BTA and how responses of students to extracurricular BTA in SMP Negeri 3 Kartasura. The purpose of this study were (1) to describe the form of program creativity of teachers in improving students ability to read the Qur'an through extracurricular approach BTA; and(2) describe the responses of students to extracurricular BTA in SMP Negeri 3 Kartasura. This research includes field resea rch (field research) with a qualitative approach. As for data collection using interviews, observation and documentation. While the method of data analysis using qualitative descriptive analysis that is in narrative form or paragraphs and not in the form of figures through the process of data collection, data reduction, and display data. Furthermore, the conclusions drawn by the deductive method is a way of thinking that departs from theory to then matched with data. Based on data analysis of the results of this study concluded that the program forms the creativity of teachers with extracurricular approach BTAyaitu system designed to classify children who can not read the Qur'an and who can read the Qur'an, then grouped into halāqah-halāqahminor consisting of 4-8 students to tadarus and mutual sema'an with friends. The task of the teacher, in addition to listening to some students who still Iqra' also monitor and supervise eachhalāqah. And the response of students with extracurricular BTA that students feel very happy with their extracurricular BTA